Digital Services Integration in Smart Cities: a Trusted Execution Environment Based Solution - Schuch, Regis; Frantz, Rafael Z.; Bocanegra, José; Roos-Frantz, Fabricia; Sawicki, Sandro; Molina-Jiménez, Carlos (Anais do Congresso Ibero-Americano em Engenharia de Software (CIbSE); 2024: Anais do XXVII Congresso Ibero-Americano em Engenharia de SoftwareDO - 10.5753/cibse.2024.28534, 2024)
This paper elucidates the use of Trusted Execution Environments as a solution to the challenges of data security and privacy within the context of digital services integration in smart cities. This type of environment is engineered to safeguard sensitive data during execution, thereby guaranteeing that tasks involving such data are performed within isolated memory compartments.